(3HZjI GdBeGd aj eYQaI GdfWb HLejY eSJbHdGJ GdCaYGds - (3GddHdj , CMeO Hf jhSa Hf Ydj Hf jhSa GdagQj, CHh LYaQ,J (B691 (3g` s
(3ChdgG (B:s
(3hLYdJ GdJUfja Ydi bSejf hNJeJ HaUdjf s
(3BNQgG (B:s
(3hCeG GdaYd GdeHfi ddeaYhd JSdjekG cKjQkG Edi jhe GdOjf s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B212s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B247s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas